A Special Cranial Nucleus (CSF-Contacting Nucleus) in Primates - Song, Si-Yuan; Zhai, Xiao-Meng; Shan, Cheng-Jing; Lu, Lei-Lei; Hong, Jia; Cao, Jun-Li; Zhang, Li-Cai (Frontiers in Neuroanatomy, 2020)
Background: There is a unique nucleus (CSF-contacting nucleus) in the brain of rat. It has been demonstrated in our previous research. The extraordinary feature of this nucleus is that it is not connected to any parenchymal organ but to the CSF. In primates, however, the presence or absence of this nucleus has not been proven. Confirmation of the presence of this nucleus in primates will provide the structural basis for brain-CSF communication and help to understand the neurohumoral regulatory mechanisms in humans. Methods: The tracer cholera toxin B subunit conjugated to horseradish peroxidase (CB-HRP) was injected into the CSF in the lateral ventricle of primate rhesus monkeys. After 48 h, the monkeys were perfused and the brain was dissected out, and sectioned for CB-HRP staining. The CB-HRP positive structures were observed under confocal and electron microscopy. The three-dimensional (3D) structure of the CB-HRP positive neurons cluster was reconstructed by computer software. Results: (1) CB-HRP labelling is confined within the ventricle, but not leakage into the brain parenchyma. (2) From the midbrain inferior colliculus superior border plane ventral to the aqueduct to the upper part of the fourth ventricle floor, a large number of CB-HRP positive neurons are consistently located, form a cluster, and are symmetrically located on both sides of the midline. (3) 3D reconstruction shows that the CB-HRP positive neurons cluster in the monkey brain occupies certain space. The rostral part is large and caudal part is thin appearing a “rivet”-like shape. (4) Under electron microscopy, the CB-HRP positive neurons show different types of synaptic connections with the non-CSF-contacting structures in the brain. Some of the processes stretch directly into the ventricle cavity. Conclusions: Same as we did in rats, the CSF-contacting nucleus is also existed in the primate brain parenchyma. We also recommend listing it as XIII pair of cranial nucleus, which is specialised in the communications between the brain and the CSF. It is significant to the completing of innervation in the organism.